A meta-analysis of the effectiveness of psychological interventions on postpartum depression in Iran, considering to the moderating role of therapeutic intervention - Oreizi, Hamidreza; zareie, Mahnaz (Advances in Nursing & Midwifery, 2017)
Abstract Aim and Background: Birth of a kid lead to disturbance of the mothers emotions and such as emotions, pleasure and even fears, and also could result the consequence which is postpartum depression. The aim of present study is meta- analysis of were researches about the effectiveness of psychological interventions on postpartum depression in Iran, considering to the Moderating role of Therapeutic intervention. Methods and Materials: In order to this, 14 researches with intended criteria to this study were selected and the metaanalysis accomplished. The meta- analysis check list was used as the tool. Calculation were done by use of 1- Hunter & Schmidt 2- Hedges & Olkin and 3- Rosenthal. Findings and Conclusions: Findings showed that effect size of the intervention on postpartum depression was 0/562. According to the conclusions, the rate of effect size of those interventions which were based on efforts and motives was more than that of interventions which theirs subjects were not motivated enough. According to the finding of the research some practical recommendations to the reduction of postpartum depression were suggested. The important point was the grater effectiveness of psychotherapy in comparison with prenatal education of mothers. Keywords: Depression, Postpartum; Psychological Techniques; Meta-Analysis